China joins global governance : cooperation and contentions - Li, Mingjiang (Lexington Books, 2012)
China Joins Global Governance: Cooperation and Contentions, edited by Mingjiang Li, provides a comprehensive and insightful examination of China's role in global governance. This insightful collection makes a significant contribution to the scholarly debate on the impacts of China's rise on the stability and future evolution of the international system.